2007
DOI: 10.1021/cb700100n
|View full text |Cite
|
Sign up to set email alerts
|

A Steric Block in Translation Caused by the Antibiotic Spectinomycin

Abstract: The widely used antibiotic spectinomycin inhibits bacterial protein synthesis by blocking translocation of messenger RNA and transfer RNAs on the ribosome. Here, we show that in crystals of the Escherichia coli 70S ribosome spectinomycin binding traps a distinct swiveling state of the head domain of the small ribosomal subunit. Spectinomycin also alters the rate and completeness of reverse translocation in vitro. These structural and biochemical data indicate that in solution spectinomycin sterically blocks sw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
149
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 137 publications
(160 citation statements)
references
References 44 publications
7
149
0
Order By: Relevance
“…Next, measuring the deviation of positions along the helical axis describing the core of the head, we localized the origins of head movement to two hinge points, located at the middle of h28 and the end of h35. These results show that h28, which has long been implicated in head rotation (11,25,(36)(37)(38)(39), is indeed involved in head movement, although not as the center of rotation.…”
Section: Discussionmentioning
confidence: 65%
See 3 more Smart Citations
“…Next, measuring the deviation of positions along the helical axis describing the core of the head, we localized the origins of head movement to two hinge points, located at the middle of h28 and the end of h35. These results show that h28, which has long been implicated in head rotation (11,25,(36)(37)(38)(39), is indeed involved in head movement, although not as the center of rotation.…”
Section: Discussionmentioning
confidence: 65%
“…Assignment of the origins of head rotation to these two hinge points was further validated by the strong correlation between the magnitudes of their deflection angles and the degree of head rotation in the different structures. Finally, our findings explain the inhibition of translocation by the antibiotic spectinomycin, which binds to the pivot point of hinge 2 (24,25,29,30). …”
mentioning
confidence: 67%
See 2 more Smart Citations
“…This is somewhat different from the ability of those aminoglycosides that inhibit protein synthesis by binding to the A site of 30S ribosomes [22], where the ability of G418 binding to RNA is assigned to its ring II [23]. Moreover, although it was recently demonstrated that G418, gentamicin and other related aminoglycosides could suppress stop codons and induce frame-shifting [24][25][26][27], only G418 was shown to inhibit virus-induced cytopathology, suggesting that the antiviral activity of G418 is different from inhibition or deregulation of translation.…”
Section: A B Cmentioning
confidence: 93%